Ultra-Brief Online Mindfulness-Based Intervention Effects on Mental Health During the Coronavirus Disease Outbreak in Malaysia: A Randomized Controlled Trial - Pheh, Kai-Shuen; Tan, Hui-Chien; Tan, Chee-Seng (Makara Human Behavior Studies in Asia, 2020)
The federal government of Malaysia recently implemented a nationwide Movement Control Order (MCO) to control the COVID-19 outbreak. However, the MCO has had a negative impact on people’s mental well-being. Interventions that can improve people’s mental health when their movement is restricted are therefore urgently needed. The present study investigated the impact of an ultra-brief online mindfulness-based intervention on mental health using a two-arm randomized controlled trial design. A total of 161 participants self-reported their distress, anxiety, psychological insecurity, and well-being at baseline and post-treatment, while 61 of them answered the same set of measures and the fear of COVID-19 scale in a follow-up study two weeks later. A multivariate analysis of covariance found the intervention reduced psychological insecurity levels measured during post-treatment. Moreover, gender, the experience of practicing mindfulness, and participants’ experiences of undergoing quarantine were found to play a role in post-treatment measures. No significant difference was found between the baseline and follow-up treatment. However, hierarchical multiple regression found that psychological insecurity measured at baseline positively predicted the level of fear after controlling for demographic variables. Overall, the findings suggest that an online mindfulness intervention is a potentially useful tool for alleviating people’s mental health difficulties